2005
DOI: 10.1021/np058075+
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 551. Isolation and Structures of Bauhiniastatins 1−4 from Bauhinia purpurea

Abstract: Bioassay-guided (P388 lymphocytic leukemia cell line) separation of extracts prepared from the leaves, stems, and pods of Bauhinia purpurea, and, in parallel, its roots, led to the isolation of four new dibenz[b,f]oxepins (2a, 3-5) named bauhiniastatins 1-4, as well as the known and related pacharin (1) as cancer cell growth inhibitors. The occurrence of oxepin derivatives in nature is quite rare. Bauhiniastatins 1-4 were found to exhibit significant growth inhibition against a minipanel of human cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 7 publications
1
76
0
2
Order By: Relevance
“…This is in agreement with Tomoko Akase et al (2011) [18] who suggested that kaempferol, an active polymethoxyflavone found in Kaempferia parviflora reduced the accumulation of visceral fat in diet induced obese rats by escalating lipid metabolism through down regulation of SREBPs [19]. The antioxidant and anti hyperlipidemic activity of bauhiniastatins falls in line with the work of Pettit et al (2005) [20] who reported the antioxidant, anti inflammatory and antineoplastic activity of bauniniastatins 1-4 in P388 lymphocytic leukemia cell line. It is well known that insulin can indirectly inspire leptin secretion through its collective effects on the metabolism of nutrients, especially on glucose utilization in adipocytes.…”
Section: Discussionsupporting
confidence: 86%
“…This is in agreement with Tomoko Akase et al (2011) [18] who suggested that kaempferol, an active polymethoxyflavone found in Kaempferia parviflora reduced the accumulation of visceral fat in diet induced obese rats by escalating lipid metabolism through down regulation of SREBPs [19]. The antioxidant and anti hyperlipidemic activity of bauhiniastatins falls in line with the work of Pettit et al (2005) [20] who reported the antioxidant, anti inflammatory and antineoplastic activity of bauniniastatins 1-4 in P388 lymphocytic leukemia cell line. It is well known that insulin can indirectly inspire leptin secretion through its collective effects on the metabolism of nutrients, especially on glucose utilization in adipocytes.…”
Section: Discussionsupporting
confidence: 86%
“…The final structural model obtained for pancratistatin is shown in Figure 1. Crystal data and experimental details follow: C 14 H 15 NO 8 , mol wt = 324.27, crystal size 0.32 × 0.13 × 0.03 mm, orthorhombic, space group P2 1 …”
Section: Crystal Structure Of Pancratistatin (1)mentioning
confidence: 99%
“…For instance, Bauhinia purpurea has shown antidiabetic, analgesic, anti-inflammatory, antipyretic, antimalarial, antifungal, cytotoxic and thyroid hormone-stimulating activities as well as free radical scavenging [6][7][8][9][10][11][12][13][14] . Phytochemical studies with Bauhinia purpurea had related the presence of several molecules which could be potential corrosion inhibitors, such as flavonoids (rutin 7 , isoquercetrin 7 , 5,6-dihydroxy-7-methoxyflavone 6-O-β-D-xylopyranoside 15 , kaempferol 16 , quercetin 16 , isohammetin 16 , strobopinin 6 , demothoxymatteucinol 6 , bauhinoxepin C-J 6 and bauhinistatins1-4 1 ) in addition to phytosterols and fatty acids 17 .…”
Section: Introductionmentioning
confidence: 99%